Designing enriched aesthetic interaction for garment comfort - Jeon, Eun Jeong (Curtin University, 2013)
This thesis describes a research through design approach to identifying comfort factors within the kinaesthetic experiences of human sensory activities and perceptions. The research explores the experience of women through the way they touch, move and feel when interacting with wool garments. The research provides (1) a body of creative work, (2) a framework of ‘enriched aesthetic interaction’ and (3) the development of design principles for the comfort and related aesthetic qualities of clothing.